2019
DOI: 10.1016/j.cgh.2018.08.069
|View full text |Cite
|
Sign up to set email alerts
|

Range of Normal Liver Stiffness and Factors Associated With Increased Stiffness Measurements in Apparently Healthy Individuals

Abstract: In a systematic review and meta-analysis of data from individual patients, we established a comprehensive set of LSM ranges, measured by TE in large cohorts of healthy individuals and persons susceptible to hepatic fibrosis. Regression analyses identified factors associated with LSMs made by TE with the medium and extra-large probes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 40 publications
3
62
0
Order By: Relevance
“…This is in line with the observation that TE may overestimate the extent of liver fibrosis in overweight individuals. 41 On the other hand, previous studies support the TE findings in that they suggested a promoting effect of obesity on liver disease development in Pi*ZZ carriers. 42,43 Another limitation of LSM, which has been carefully addressed in our study, is its potential affection by hepatic congestion (eg, caused by right-sided heart failure).…”
Section: Discussionmentioning
confidence: 68%
“…This is in line with the observation that TE may overestimate the extent of liver fibrosis in overweight individuals. 41 On the other hand, previous studies support the TE findings in that they suggested a promoting effect of obesity on liver disease development in Pi*ZZ carriers. 42,43 Another limitation of LSM, which has been carefully addressed in our study, is its potential affection by hepatic congestion (eg, caused by right-sided heart failure).…”
Section: Discussionmentioning
confidence: 68%
“…In presumably healthy individuals, several studies have demonstrated a significant increase in LSM in those with hepatic steatosis on ultrasound compared to those without steatosis. 3,[33][34][35] In our study, we have extended this observation to the paediatric population.…”
Section: Sensitivity Analysis Including All Individuals In Ipd Cohortmentioning
confidence: 72%
“…14 We kept items focused on the representativeness of the cases and ascertainment of outcome and removed items that related to the selection of the controls and comparability. This tool has been applied in many previous publications, 3,[15][16][17][18] with good consistency among reviewers. The assessment of methodologic quality for the 10 included cohorts and the overall risk of bias for these cohorts are found in Supplemental Information.…”
Section: Assessment Of Methodologic Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis collected data on TE values in healthy individuals identifying 26 studies and a total of 16,082 participants [50]. The mean liver stiffness in nonobese individuals was 4.68 kPa, with increased stiffness measurements in individuals with diabetes, increasing waist circumference, obesity, elevated serum transaminases or hypertension.…”
Section: Other Studiesmentioning
confidence: 99%